ChemInform Abstract: Catalyst‐ and Metal‐Free Rapid Functionalizations of Alkynes Using TsNBr2. Issue 46 (24th October 2013) - Chawla, Ruchi; Singh, Atul K.; Yadav, Lal Dhar S.
Abstract A rapid, catalyst‐free method for the conversion of terminal and internal alkynes to α, α‐dibromoalkanones is presented using TosNBr2 as the reagent in the presence of water.